2019
DOI: 10.1016/j.conctc.2019.100465
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of early low-dose aspirin in diabetes: A phase III multicentre double-blinded placebo-controlled randomised trial of aspirin therapy initiated in the first trimester of diabetes pregnancy

Abstract: BackgroundPreeclampsia, preterm birth and low birth weight represent key contributing factors to perinatal morbidity and mortality. Pregnancies complicated by type 1 and type 2 diabetes are at increased risk of these complications, which are purported to be largely attributed to placental dysfunction. Studies investigating a potential role for aspirin therapy in optimizing perinatal outcome have consistently failed to demonstrate a benefit among women with pre-existing diabetes, and yet widespread aspirin admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The results of the systematic review are shown in Figure S1. Of the 1475 potentially relevant studies, 67 16,17,23–87 fulfilled the inclusion criteria (Table 1). Two hundred and ten outcomes were extracted from the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the systematic review are shown in Figure S1. Of the 1475 potentially relevant studies, 67 16,17,23–87 fulfilled the inclusion criteria (Table 1). Two hundred and ten outcomes were extracted from the studies.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest there is a need for further trials within this high-risk subgroup of women, particularly addressing issues around optimal aspirin dosage requirements and the possible implications of differing stages of disease, comorbidities and type 1 vs type 2 DM on effectiveness of prophylaxis. A multicentre phase III RCT in Ireland is underway and due for recruitment completion in early 2022, 40 of which we will eagerly await results.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the role of low-dose aspirin therapy in preventing preeclampsia that included a subgroup of pregnant women with preexisting DM failed to demonstrate a benefit among women with preexisting DM, and the women were all recruited in the second trimester [50]. In a recent phase III double-blinded, placebo-controlled randomized multicenter clinical trial conducted in Ireland, researchers examined the effect of low-dose aspirin therapy from the first trimester until 36 GW on perinatal outcome in women with established pre-pregnancy DM, hypothesizing that aspirin therapy will reduce complications mediated by placental dysfunction and improve perinatal outcomes [51]. Low-dose aspirin therapy to prevent the onset of preeclampsia in pregnant women with DM might decrease the onset of FGR as a second-order effect.…”
Section: Discussionmentioning
confidence: 99%